Levels of IL-18 and IL-28 in thalassemia patients with viral infections - Kadhim, Maytham Khazaal; Ghaima, Kais Kassim (Edelweiss Applied Science and Technology, 2024)
Thalassemia is an inherited hemoglobin disorder that requires lifelong medical care. Patients with thalassemia are very prone to infections by viruses, which may exacerbate their condition, leading to serious complications. Knowledge of the immune response in these patients could be very helpful in the effective management of their disease. The levels of IL-18 and IL-28 were evaluated in thalassemia patients with different viral infections to assess their potential as biomarkers and therapeutic targets. This was a retrospective analysis of clinical data on thalassemia patients with viral infections. Demographic, clinical, laboratory, IL-18, and IL-28 data at baseline were included in the study. In the present study, the authors assessed the correlations between interleukin levels, viral infection, treatment response, and overall survival. The study enrolled 250 patients with thalassemia and different viral infections. In these patients, the levels of IL-18 and IL-28 were found to be elevated with a significant correlation to viral load. Thus, a higher baseline interleukin level predicted a better treatment response and overall survival. Elevations in IL-18 and IL-28 in thalassemia patients with associated viral infections likely indicate immune system activation. Their correlation with viral load and treatment outcomes suggests their potential as biomarkers and targets for therapy. These findings further underline the protective role of IL-18 and IL-28, hence contributing to enhanced survival rates of the patients. Further studies for translation of these insights into practice may help modify clinical care for better patient outcomes.